TEACHING PRESENTATION SKILLS IN ENGLISH LESSONS (Western European Journal of Linguistics and Education, 2023)
Today, the need to teach the art of public speaking is prerequisite skills for the training of future engineers and economists. The lack of special disciplines aimed at developing presentation skills leads to the fact that the majority of university graduates are not ready to speak at scientific conferences and professional meetings. Therefore, our course "Practical English" which includes the formation of skills of communicative speech activity is the best suited for these purposes. In this article, we will share our experiences in teaching preparation skills of presentation activities of undergraduates of technical areas English lessons.